Stress and Coping Strategies among Management and Science University Students: A Qualitative Study - AAN, Redhwan; AR, Sami; AJ, Karim; R, Chan; MI, Zaleha (IIUM Medical Journal Malaysia, 2009)
Introduction: This study aimed to explore the associated factors related to causes of stress and coping strategies among university students. Materials and Methods: As a focus group discussion, it was universal sampling, conducted among 39 of Medical Science and Biomedicine students on their second semester from Management and Science University (MSU), Shah Alam, Malaysia. Three issues were discussed: firstly, how they define the stress; secondly, what the most important causes of stress in their life are; and thirdly, how they cope with stress. Verbal consent was obtained from all participants. Due to the small sample size, the data was analyzed manually. Results: Total of participants were 39 students, their age ranged from 21 to 26 years. Seventeen (43.6%) of the students were 21 years old and the majority were female 31 (79.5%). The most important causes of stress reported by the students were financial, lack of sleep, and family problems. In terms of coping with stress, the students were able to describe a variety of strategies to cope with their stressful situations. These included counseling services, doing meditation, sharing of problems, getting adequate sleep, and going out with friends. Conclusion: Most of the students defined stress as “a mental condition”. Lack of sleep, financial, and family problems were the most causes of stress among students. The students were able to identify some strategies to cope with stress.